2022
DOI: 10.3390/ijerph192315725
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Traumatic Dental Injuries in the Permanent Dentition: A Three-Year Retrospective Overview Study at the University Dental Clinic of Vienna

Abstract: The aim of this study was to retrospectively analyze the prevalence and patterns of traumatic dental injuries (TDIs) in permanent teeth at the University Dental Clinic of Vienna and examine influential variables. The study included all patients with dental trauma in permanent teeth who presented at the University Dental Clinic of Vienna (Austria) between 2014 and 2016. Dental records, including age, gender, location of trauma, type of trauma, cause of TDI, and location of the traumatic incident, were obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Even though there seems to be a different result compared with us, we still got a significantly lower (5.12%) complication rate compared with the previous reports. Besides, Schneider and Stern previously reported a rarely low complication rate of 5% when the teeth in the fracture line were preserved in a study including 199 cases 21 . Based on the analysis, they strongly suggested that appropriate antibiotic therapy should be taken in the treatment procedure, which could allow the teeth to be successfully preserved in the fracture healing procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though there seems to be a different result compared with us, we still got a significantly lower (5.12%) complication rate compared with the previous reports. Besides, Schneider and Stern previously reported a rarely low complication rate of 5% when the teeth in the fracture line were preserved in a study including 199 cases 21 . Based on the analysis, they strongly suggested that appropriate antibiotic therapy should be taken in the treatment procedure, which could allow the teeth to be successfully preserved in the fracture healing procedure.…”
Section: Discussionmentioning
confidence: 98%
“…were preserved in a study including 199 cases. 21 Based on the analysis, they strongly suggested that appropriate antibiotic therapy should be taken in the treatment procedure, which could allow the teeth to be successfully preserved in the fracture healing procedure. Also, the more widely arranged study, which is a study including 327 mandibular fracture patients, which was led by Chuong et al, 22 also reported that the complication rate was without significant difference among patients who retained or extracted the fracture line affected teeth.…”
Section: Discussionmentioning
confidence: 99%
“…https://www.nucleodoconhecimento.com.br 142 RC: 151714 Disponível em: https://www.nucleodoconhecimento.com.br/odontologia/reabilitacao-estetica Traumas acidentais, brigas de rua e esportes de contato podem levar a fraturas coronárias, que vão desde a perda mínima do esmalte até fraturas complexas, envolvendo o tecido pulpar (Lembacher et al, 2022;Roettger et al, 2018). O tipo e a localização da fratura dependem da idade do paciente, quantidade de força e direção do golpe (Slayton e Palmer, 2019).…”
Section: Introductionunclassified